Quantification of the UPDRS rigidity scale - Patrick, S.K.; Denington, A.A.; Gauthier, M.J.A.; Gillard, D.M.; Prochazka, A. (IEEE transactions on neural systems and rehabilitation engineering, 2001)
In the clinical setting, Parkinsonian rigidity is assessed using subjective rating scales such as that of the Unified Parkinson's Disease Rating System (UPDRS). However, such scales are susceptible to problems of sensitivity and reliability. Here, we evaluate the reliability and validity of a device designed to quantify Parkinsonian rigidity at the elbow and the wrist. The method essentially quantifies the clinical examination and employs small sensors to monitor forces and angular displacements imposed by the clinician onto the limb segment distal to the joint being evaluated. Force and displacement data are used to calculate elastic and viscous stiffnesses and their vectorial sum, mechanical impedance. Interexaminer agreement of measures of mechanical impedance in subjects with Parkinson's disease was comparable to that of clinical UPDRS scores. Examiners tended to overrate rigidity on the UPDRS scale during reinforcement manoeuvres. Mechanical impedance was nonlinearly related to UPDRS ratings of rigidity at the elbow and wrist; characterization of such relationships allows interpretation of impedance measurements in terms of the clinical rating scales.